(untitled) (Psychology Travelogs, 2023)
The article raises the relevance of the problem of fabbing in modern society. The paper provides a theoretical analysis of the concepts of "fabbing" and "Internet addiction". Also, the main causes and characteristic features of this phenomenon are described, and the consequences of this problem are revealed. The author analyzes the negative impact of fabbing on the individual, his or her psyche, and interpersonal communication. The authors of the article emphasize that many researchers note that society is increasingly alienated from real life, communication, work, and study and is moving into virtual reality, which in turn has a negative impact on physical and emotional life. Modern people are changing, changing their life priorities, values, and goals, and spending more and more of their time online. This creates a distorted view of communication and interaction, because a person online can show themselves the way they want others to perceive them, they create an image that others may not notice in real life. The authors of the article draw attention to the fact that the issue of fabbing is not sufficiently researched, so the question of its impact on the individual and society as a whole remains open. To prevent and combat fabbing, the authors propose to expand the ways of researching this phenomenon using psychology and other social sciences. It is important to raise people’s awareness that wealth, success, and happiness are not always portrayed truthfully on social media, and that real life is more important than the ideal life on the Internet. Thus, the article is dedicated to the actual problem of faking, which requires attention and understanding. The authors emphasize that the globalization of the faking phenomenon requires a detailed study and research of ways to rationalize the online presence and raise people’s awareness of the real value of life.